2021
DOI: 10.1111/jeb.13791
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of gut microbiota with a broad‐spectrum antibiotic does not impair maternal care in the European earwig

Abstract: The microbes residing within the gut of an animal host often increase their own fitness by modifying their host's physiological, reproductive, and behavioural functions. Whereas recent studies suggest that they may also shape host sociality and therefore have critical effects on animal social evolution, the impact of the gut microbiota on maternal care remains unexplored. This is surprising, as this behaviour is widespread among animals, often determines the fitness of both juveniles and parents, and is essent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 101 publications
(141 reference statements)
1
9
0
Order By: Relevance
“…In honeybees, for instance, cadmium exposure alters the microbiome and some bacterial strains can bioaccumulate this pollutant, making bees more resilient to cadmium (Rothman et al 2019). Investigating the microbiome composition (Van Meyel, Devers, Dupont, et al 2021) and its putative role in earwig cadmium resistance would be of great value.…”
Section: Discussionmentioning
confidence: 99%
“…In honeybees, for instance, cadmium exposure alters the microbiome and some bacterial strains can bioaccumulate this pollutant, making bees more resilient to cadmium (Rothman et al 2019). Investigating the microbiome composition (Van Meyel, Devers, Dupont, et al 2021) and its putative role in earwig cadmium resistance would be of great value.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antibiotics are frequently used to prevent bacterial infection of larval honeybees, but prolonged use of antibiotics leads to disruption of gut microbial homeostasis, increasing susceptibility to opportunistic pathogens and affecting honeybee health [ 76 ]. Meyel et al found that after feeding on rifampicin by European earwig larvae, the homeostasis of the host’s gut microbes was disrupted, and the weight of eggs and larvae decreased [ 77 ]. Powell et al found that Apis mellifera ingested tylosin tartrate, which significantly increased their susceptibility to S. marcescens [ 78 ].…”
Section: Negative Effects Of Gut Microbes On the Hostmentioning
confidence: 99%
“…(3) We measured the level of egg defence just after the video recording. Egg defence represents the mother's endurance in defending her clutch and herself against predators (Van Meyel et al 2021). This was measured by gently opening each Petri dish, standardly poking the pronotum of the mother with a glass capillary (1 poke per second) and then recording the number of pokes required for her to move more than one body length away from its initial position.…”
Section: Expression Of Maternal Egg Carementioning
confidence: 99%